Analisis Pengaruh Social Media Marketing, E-Service Quality, Dan Kepercayaan Merek Terhadap Repurchase Intention Dengan Kepuasan Pelanggan Sebagai Variabel Intervening: Studi Pada Pengguna Produk Luxcrime Di Indonesia - Felicia Emmeline; Amie Kusumawardhani (Faculty of Economics and Business Diponegoro University, 2025)
Social media is one of the marketing platforms that is considered effective as an important means for consumers to gather information on which to base decisions. This encourages the beauty and facial care industry in Indonesia to utilize their social media so that they can continue to compete to dominate the market. Luxcrime is one of the well-known local beauty and facial care brands that has successfully implemented it. This study aims to analyze the factors that influence repurchase intention in Luxcrime product users in Indonesia through social media marketing, e-service quality, and brand trust by considering customer satisfaction as a mediator in the relationship.This research method applied an online survey of Luxcrime product users in Indonesia which resulted in data of 160 respondents. The results of the questionnaire data collection that has been obtained, analyzed quantitatively and structurally using the SEM (Structural Equation Modeling) method using the AMOS (Analysis Moment of Structural) program.The findings in this study indicate that E-Service Quality, Social Media Marketing, Brand Trust have a positive and significant effect on Customer Satisfaction. Then, Customer Satisfaction has a positive and significant effect on Repurchase Intention. However, there is a hypothesis that has a positive but insignificant effect between E-Service Quality and Brand Trust on Repurchase Intention.